Rethinking patient's chief complaint, research contributions developed by medical students to person-centered care - Mariana Sawchuk Moura Marques Antunes; Pedro Puccioni de Oliveira Lyra; Julia Pinho de Mattos; Deisianny dos Santos Ferreira; Luiza Brandão Catharina; Julia da Matta Xavier Pinheiro Machado; Manuela Wendling Russo Lourenço; Luísa Leite Vaz da Silva; Victor Hugo Paixão Ximenes; Manuela Rodrigues Müller (Escola Bahiana de Medicina e Saúde Pública, 2022)
INTRODUCTION: Traditionally, anamnesis, or medical interviews, have been the main tools in diagnosing health issues and indicating therapeutic intervention. Medical interviews perform clinical methods and hence medical theory. OBJECTIVE: In this paper, we will present a learning experience process gained during an introductory course on research. METHODOLOGY: Based on a clinical report designed for the purposes of investigation, a group of students and an advisor analyzed the role of the chief complaint in providing healthcare. RESULTS: Students noticed the case did not express the chief complaint of the patient. In addition, there was difficulty in articulating social and biological data in the report. Such findings were discussed by the group considering the literature on medical interviews and the medical anthropology framework in order to broaden their understanding of subjective and sociocultural aspects of illness. CONCLUSION: Group discussions about the case and the literature made it possible to expand the students' understanding. We argue that taking into account the main complaints can reveal a complex range of sociocultural meanings and webs relevant to understanding the health concepts and practices of patients and their microsocial groups. In doing so, we hope to contribute to the debates around medical education and the appreciation of sociocultural aspects in health practices. And, thus, enrich the caregiver-patient relationship towards person-centered care.